Relationship between patient safety culture and safety performance in nursing: The role of safety behaviour - Shaohua, H. (2021)
Aim: The aim of this work is to test the mediator role of patient safety behaviour between safety culture and safety performance among nurses. Methods: This cross-sectional study was carried out between September and December 2017 in the nursing units of 10 primary hospitals, two secondary hospitals and two tertiary hospitals in Anhui Province, China. Results: The study participants comprised 79 RNs from primary hospitals, 147 RNs from secondary hospitals and 242 RNs from tertiary hospitals. Most were female (97.6%) and married (73.1%), and their ages ranged from less than 25 years to retirement age. The sample included nurses working in several departments, including medicine (27.1%), surgery (14.3%), emergency (11.5%) and ICU (9%). Structural equation model analysis results showed that espoused values directly affected safety performance, and practised values affected safety performance through safety behaviour. Conclusion: Our hypothetical model noted that safety behaviour is a positive mediating factor of practised safety values affecting safety performance, suggesting that Chinese nursing managers should construct a patient safety culture that is guided and driven by appropriate values, which will ultimately be externalized as nurses' daily behaviour.